Driving Sustainable Competitiveness through Market and Technology Orientation in Coffee Shops - Hanif Shidqi; Desman Hidayat (Journal of Business, Management, and Social Studies, 2026)
This research aims to determine the influence of market orientation and technology orientation on sustainable competitive advantage with product innovation (directly or as a mediating variable). This study deployed a quantitative, explanatory survey design analyzing data from 63 Indonesian consumers who engaged with TikTok Live using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS. The structural framework evaluated dual information-processing routes (specifically central-route argument quality, peripheral-route streamer credibility and attractiveness, and interactive engagement) to test their direct impacts on purchase intention. The test results prove that market orientation and technology orientation have a positive and significant influence on sustainable competitive advantage with product innovation (directly or as a mediating variable) in coffee shops in Jabodetabek. Grounded in the Elaboration Likelihood Model (ELM), this study addresses existing contradictions in social commerce literature by empirically isolating how dual information-processing routes (central route argument quality versus peripheral route credibility and attractiveness) and real-time interactivity function together within the rapidly growing, highly interactive TikTok Shop live-streaming ecosystem in Indonesia.